Desain Antarmuka E-Commerce Tema Natal untuk Layanan Virtual Office Menggunakan Design Thinking - Adhinata Kusuma, Rendy; Witanti, Wina; Yuniarti, Rezki (Jurnal Algoritma, 2025)
Baros Information Technology Creative (BITC) is a virtual office service provider based in Cimahi that requires adaptive, engaging, and seasonally contextual user interface (UI) and user experience (UX) support to enhance user appeal and engagement. This study aims to design the UI/UX of BITC’s virtual office e-commerce website with a Christmas theme using the Design Thinking methodology. This approach was selected for its iterative and user-centered nature, enabling in-depth exploration of user needs and the development of contextually relevant design solutions. The design process was carried out through five stages—empathize, define, ideate, prototype, and test—involving five respondents selected through purposive sampling. User requirements were gathered via interviews and surveys, then translated into design concepts visualized through interactive prototypes. Usability testing was conducted using the System Usability Scale (SUS), adapted to suit the seasonal theme context. The test results yielded an average SUS score of 82, categorized as “good” with an “excellent” level of acceptance, indicating that the resulting design is user-friendly, visually relevant, and supports seasonal promotional strategies. This study reinforces previous findings that user-centered design approaches are effective in improving interface quality and user experience, while also offering a novel contribution through the application of seasonal themes within the context of professional digital services.